Insomnia – A Heterogenic Disorder Often Comorbid With Psychological and Somatic Disorders and Diseases: A Narrative Review With Focus on Diagnostic and Treatment Challenges - Bjorvatn, Bjørn; Jernelöv, Susanna; Pallesen, Ståle (Frontiers in Psychology, 2021)
Patients with insomnia complain of problems with sleep onset or sleep maintenance or early morning awakenings, or a combination of these, despite adequate opportunity and circumstances for sleep. In addition, to fulfill the diagnostic criteria for insomnia the complaints need to be associated with negative daytime consequences. For chronic insomnia, the symptoms are required to be present at least 3 days per week for a duration of at least 3 months. Lastly, for insomnia to be defined as a disorder, the sleep complaints and daytime symptoms should not be better explained by another sleep disorder. This criterion represents a diagnostic challenge, since patients suffering from other sleep disorders often complain of insomnia symptoms. For instance, insomnia symptoms are common in e.g., obstructive sleep apnea and circadian rhythm sleep-wake disorders. It may sometimes be difficult to disentangle whether the patient suffers from insomnia disorder or whether the insomnia symptoms are purely due to another sleep disorder. Furthermore, insomnia disorder may be comorbid with other sleep disorders in some patients, e.g., comorbid insomnia and sleep apnea (COMISA). In addition, insomnia disorder is often comorbid with psychological or somatic disorders and diseases. Thus, a thorough assessment is necessary for correct diagnostics. For chronic insomnia disorder, treatment-of-choice is cognitive behavioral therapy, and such treatment is also effective when the insomnia disorder appears comorbid with other diagnoses. Furthermore, studies suggest that insomnia is a heterogenic disorder with many different phenotypes or subtypes. Different insomnia subtypes may respond differently to treatment, but more research on this issue is warranted. Also, the role of comorbidity on treatment outcome is understudied. This review is part of a Research Topic on insomnia launched by Frontiers and focuses on diagnostic and treatment challenges of the disorder. The review aims to stimulate to more research into the bidirectional associations and interactions between insomnia disorder and other sleep, psychological, and somatic disorders/diseases.